Discovery of novel isatin-based thiosemicarbazones: synthesis, antibacterial, antifungal, and antimycobacterial screening - Maryam Hassan; Ramtin Ghaffari; Soroush Sardari; Yekta Farmahini Farahani; Shohreh Mohebbi (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: A group of thiosemicarbazones were prepared and their structures were confirmed by spectroscopic methods such as IR and H-NMR, mass spectrometry and also analytical method like elemental analysis. The synthesized semicarbazones were then assessed for their inhibitory activity against bacterial strains including Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus epidermidis, Bacillus cereus, Salmonella species, Enterobacter faecalis, methicillin-resistant Staphylococcus aureus, and fungi such as Candida albicans and Aspergillus niger. Experimental approach: The schiff bases of isatin (2a-j) were prepared by a condensation reaction between thiosemicarbazide and substituted N-aryl isatins leading to the desired thiosemicarbazones with exquisite purity. Findings / Results: The results disclosed that all compounds have noticeable inhibitory activity. Compounds 2a, 2b, 2c, 2g, and 2h were among the most potent derivatives against Gram negative bacteria and fungi. Besides, the activity of theses compounds were tested against Mycobacterium bovis bacillus Calmette-Guerin (M. bovis BCG). The antimycobacterial activity indicated compounds 2e and 2j are highly active against M. bovis BCG (minimum inhibitory concentration < 3.9 μg/mL). Among fluorinated structures, compounds 2a and 2j showed the best activities against M. bovis BCG. Conclusion and implications: To sum up, amongst the 10 synthesized compounds, fluorinated derivatives exhibited remarkable activities against both gram negative strains and candida albicans microorganism. Therefore, they should be considered as a clue for further modifications in next investigations. Furthermore, inserting a small/medium size halogen atom with electron-withdrawing and lipophilic properties increases anti- salmonella activity of these compounds and moreover 2-halogenated semithiocarbazones presented promising antimycobacterial activity.